The continuous development of a complete and objective automatic grading system of facial signs from selfie pictures: Asian validation study and application to women of three ethnic origins, differently aged. Issue 2 (20th July 2020) - Flament, Frederic; Lee, Yang Won; Lee, Dong Hun; Passeron, Thierry; Zhang, Yuze; Jiang, Ruowei; Prunel, Anne; Dwivedi, Seema; Kroely, Camille; Park, Youn Jung; Chuberre, Bertrand; Aarabi, Parham
Abstract: Objective: To evaluate the capacity of the automatic detection system to accurately grade, from smartphones' selfie pictures, the severity of seven new facial signs added to the nine previously integrated. Methods: A two‐step approach was conducted: first, to check on 112 Korean women, how the AI‐based automatic grading system may correlate with dermatological assessments, taken as reference; second, to confirm on 1140 women of three ancestries (African, Asian, and Caucasian) the relevance of the newly input facial signs. Results: The sixteen specific Asian facial signs, detected automatically, were found significantly ( P < .0001) highly correlated with the clinical evaluations made by two Korean dermatologists (wrinkles: r = .90; sagging: r = .75‐.95; vascular: r = .85; pores: r = .60; pigmentation: r = .50‐.80). When applied at a larger scale on women of different ethnicities, new signs were found of good accuracy and reproducibility, albeit depending on ethnicity. Due to contrast with the innate skin complexion, the facial signs dealing with skin pigmentation were found of a much higher relevance among Asian women than African or Caucasian women. The automatic gradings were even found of a slightly higher accuracy than the clinical gradings. Conclusion: The previously used automatic grading system is now completed by adding new facial signs apt at being detected. The continuous development is now integrating some limitations with regard to the constitutive skin complexion of the self‐pictured subjects. Presenting reproducible assessments, highly correlated with medical grading, this system could change tremendously clinical researches, like in epidemiological studies, where it offers an easy, fast, affordable, and confidential approach in the objective quantification of facial signs.